Speech-to-Text-based Life Log System for Smartphones - Seo, Dongmahn; Hong, Seung-gil; Song, Gyuwon; Kim, Suhyun (2014 IEEE INTERNATIONAL CONFERENCE ON CONSUMER ELECTRONICS (ICCE), 2014)
In this paper, we propose a life log system which provides a real-time voice recording with a speech-to-text feature over smartphone environments. The proposed system records data of user life using a microphone of smartphone. Recorded data are sent to a server, analyzed, and stored. Recorded data are dictated using a speech-to-text service, and saved as text files. The proposed system is implemented as a prototype system and evaluated. Users of our system are able to search their life log sound files using text.